Secessionist Conflicts: Unresolved Legacies of United Nations Trusteeship. Issue 2 (15th March 2022) - Distler, Werner; Heise, Julius
ABSTRACT: We argue that the United Nations Trusteeship System after World War II, in its attempts to release states into independence, was simultaneously complicit in perpetuating secessionist conflicts, with which former trust territories continue to struggle until today. Secessionism was framed as a threat to state-building and not as an expression of self-determination. We use a Critical Security Studies framework and compare the conflict on Ewe/Togoland unification in bordering regions of the British Gold Cost and the Trusteeship Territories of Togoland (1950s), with the conflict on secessionism of Bougainville from the Territory of Papua and New Guinea (1970s).